2021
DOI: 10.1111/ajt.16766
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune response and safety of two-dose SARS-CoV-2 mRNA-1273 vaccine in solid organ transplant recipients

Abstract: Solid organ transplant recipients are at high risk of severe disease from COVID‐19. We assessed the immunogenicity of mRNA‐1273 vaccine using a combination of antibody testing, surrogate neutralization assays, and T cell assays. Patients were immunized with two doses of vaccine and immunogenicity assessed after each dose using the above tests. CD4+ and CD8+ T cell responses were assessed in a subset using flow‐cytometry. A total of 127 patients were enrolled of which 110 provided serum at all time points. A po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
172
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(196 citation statements)
references
References 33 publications
21
172
0
3
Order By: Relevance
“…Most studies assessed anti-SARS-CoV-2 immunity through an immunoassay to detect antibodies targeted at the spike protein, including some targeting specifically the receptor-binding domain (RBD) of the spike protein. Thirty studies reported neutralization assay results in addition to anti-SARS-CoV-2 antibody assays [ 34 , 37 , 41 , 48 , 51 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ]. Thirty-one studies provided data on cellular immunity [ 17 , 21 , 22 , 34 , 37 , 41 , 45 , 46 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , 72 , [74] , [75] , [76] , [77] , [79] , [80] , [81] , [82] , [83] , [84] ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies assessed anti-SARS-CoV-2 immunity through an immunoassay to detect antibodies targeted at the spike protein, including some targeting specifically the receptor-binding domain (RBD) of the spike protein. Thirty studies reported neutralization assay results in addition to anti-SARS-CoV-2 antibody assays [ 34 , 37 , 41 , 48 , 51 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ]. Thirty-one studies provided data on cellular immunity [ 17 , 21 , 22 , 34 , 37 , 41 , 45 , 46 , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , 72 , [74] , [75] , [76] , [77] , [79] , [80] , [81] , [82] , [83] , [84] ].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies described immunogenicity across various solid organ transplant populations ( n = 5974), mostly in kidney transplant recipients ( n = 3534, 59.2%) ( Table S5 ) [ 18 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , 29 , 34 , 40 , [56] , [57] , [58] ], [ 62 , 63 , 65 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 , 120 , 126 ], [ [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] ]. Twenty-four of those studies included a control group representing overall 1399 participants [ 21 , 34 , 57 , 63 , 66 , 69 , 72 , 73 , 75 , 79 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are current attempts to enhance the overall magnitude and durability of immune responses, for example by altering vaccine dosing and boosting regimens. Optimization of prime-boost regimens may obviate the need for "third boosters," which are now recommended for people over 65 years old, as well as patients at high risk of severe illness, including immunosuppressed individuals (8,9). Importantly, the waning of immunity several months post-vaccination is associated with increase in the number of breakthrough infections (10), leading experts to consider additional boosters for the general population.…”
Section: Introductionmentioning
confidence: 99%